APLIKASI MICROBUBBLE GENERATOR POROUS-VENTURI PADA PENGOLAHAN AIR LIMBAH BUATAN - Lathifa Putri Afisna; Wibawa Endra Juwana (KURVATEK, 2020)
Abstract The limitation of clean water due to water pollution from household and industrial waste, it is necessary to develop an environmentally friendly waste water treatment technology and installation easily. Microbubble generator (MBG) is used to produce oxygen needed by bacteria to decompose wastewater. In this study a porous-venturi MBG was designed to be installed in an artificial wastewater pool. The parameters to be measured are mass transfer coefficient (KLa), dissolved oxygen (DO) and chemical oxygen demand (COD). KLa values ​​are measured using DO meters mounted 60 cm and 180 cm from the MBG. Liquid flowrate is set 30-80 lpm and gas flowrate is set 0.1, 0.4 and 1 lpm. Based on the results of the study, the increase in liquid flowrate at all measurement distances causes the KLa value increase too, but the increase in gas flowrate does not significantly affect. The higher DO value will reduce COD value in artificial waste water below to 100 mg /L. Keywords :Microbubble, venturi, DO, COD, KLa